LBA3 Nivolumab (NIVO) + platinum-doublet chemotherapy (chemo) vs chemo as first-line (1L) treatment (tx) for advanced non-small cell lung cancer (aNSCLC): CheckMate 227 - part 2 final analysis. (15th December 2019) - Paz-Ares, L; Ciuleanu, T E; Yu, X; Salman, P; Pluzanski, A; Nagrial, A; Havel, L; Kowalyszyn, R; Audigier-Valette, C; Wu, Y-L; Borghaei, H; Hellmann, M D; et al.
Abstract: Background: Immunotherapy with or without chemo has improved survival vs chemo in 1L aNSCLC. NIVO + chemo showed encouraging activity in a phase 1 study in this setting. CheckMate 227 is a multi-part, randomized, open-label, phase 3 study evaluating NIVO-based regimens vs chemo. We present final results from Part 2, which evaluated NIVO + chemo vs chemo in 1L aNSCLC. Methods: Pts (N = 755) with chemo-naive, stage IV or recurrent NSCLC, ECOG PS 0–1, and no sensitizing EGFR/ALK alterations were randomized 1:1 to receive every 3 weeks NIVO 360 mg + chemo or chemo. Pts were stratified by histology (squamous [SQ] vs non-squamous [NSQ]), sex, and PD-L1 expression (< 1% vs ≥ 1%). Chemo was histology-based and continued for up to 4 cycles; pts with NSQ NSCLC could receive pemetrexed maintenance. Pts were treated until progression, unacceptable toxicity, or for 2 years for NIVO. The primary endpoint was overall survival (OS) with NIVO + chemo vs chemo in NSQ NSCLC. OS in all randomized pts (NSQ and SQ) was a secondary hierarchical endpoint. Results: Baseline characteristics were generally balanced. Minimum follow-up was 19.5 mo. In pts with NSQ NSCLC, no statistically significant improvement in OS was seen with NIVO + chemo vs chemo (HR, 0.86 [95.62% CI, 0.69–1.08; P = 0.1859]); median OS was 18.8 mo vs 15.6 mo; 12-mo OS rates were 67.3% vs 59.2%. HR for OS was 0.81 (95% CI, 0.67–0.97) in all randomized pts; 0.69 (95% CI, 0.50–0.97) in pts with SQ NSCLC. Progression-free survival and objective response rates favored NIVO + chemo in NSQ, SQ, and all randomized pts (table). Grade 3–4 tx-related adverse events occurred in 45% and 35% of all pts treated with NIVO + chemo and chemo, respectively. Conclusion: CheckMate 227 Part 2 did not meet the primary endpoint of OS for NIVO + chemo vs chemo in NSQ NSCLC. Descriptive analyses showed longer OS with NIVO + chemo in all randomized pts and SQ NSCLC. No new safety signals were observed. Clinical trial identification: NCT02477826; Release date: June 23, 2015. Editorial acknowledgement: Writing and editorial assistance was provided by Namiko Abe, PhD, of Caudex, funded by Bristol-Myers Squibb. Legal entity responsible for the study: Bristol-Myers Squibb. Funding: Bristol-Myers Squibb. Disclosure: L. Paz-Ares: Honoraria (self): Roche, MSD, Lilly, Novartis, Boehringer Ingelheim, AstraZeneca, Amgen, Sanofi, Pharmamar, Pfizer, Bristol-Myers Squibb, Merck, Takeda, Celgene, Servier, Sysmex, Incyte, Ipsen, Adacap, Bayer, Blueprint; Leadership role: Altum Sequencing; Research grant / Funding (institution): MSD, AstraZeneca, Pfizer, Bristol-Myers Squibb; Officer / Board of Directors: Genomica. T.E. Ciuleanu: Advisory / Consultancy: Astellas, Janssen, Bristol-Myers Squibb, Merck Serono, Amgen, Roche, Pfizer, Boehringer Ingelheim, Lilly, AstraZeneca, MSD, Sanofi, Novartis, Servier, AD Pharma. A. Pluzanski: Advisory / Consultancy: AstraZeneca, Boehringer Ingelheim, Roche; Speaker Bureau / Expert testimony: AstraZeneca, Boehringer Ingelheim, Bristol-Myers Squibb, MSD, Roche, Takeda; Travel / Accommodation / Expenses: AstraZeneca, Boehringer Ingelheim, Bristol-Myers Squibb, MSD, Roche. A. Nagrial: Advisory / Consultancy: AstraZeneca, Bristol-Myers Squibb, Merck Sharp & Dohme, Novartis, Roche; Research grant / Funding (institution): Astra Zeneca, Bristol-Myers Squibb, Merck Sharp & Dohme, Novartis, Roche. R. Kowalyszyn: Advisory / Consultancy: Astellas, Bristol-Myers Squibb, MSD; Speaker Bureau / Expert testimony: Bristol-Myers Squibb, MSD, Novartis; Research grant / Funding (institution): Novartis; Travel / Accommodation / Expenses: Bristol-Myers Squibb, Lilly, MSD, Pfizer, Roche. C. Audigier-Valette: Honoraria (self): AbbVie, Pfizer; Honoraria (institution): Roche, MSD, Bristol-Myers Squibb, AstraZeneca; Advisory / Consultancy: Roche, MSD, Bristol-Myers Squibb, AstraZeneca, AbbVie, Pfizer. Y-L. Wu: Honoraria (self): AstraZeneca, Boehringer Ingelheim, BMS, Eli Lilly, MSD, Pfizer, Roche; Advisory / Consultancy: AstraZeneca, Boehringer Ingelheim, Roche; Research grant / Funding (institution): AstraZeneca, Boehringer Ingelheim, BMS, Roche; Non-remunerated activity/ies: AstraZeneca, Boehringer Ingelheim, BMS, Eli Lilly, MSD, Pfizer, Roche. H. Borghaei: Honoraria (self): University of Pennsylvania, CAR T Program, Takeda [Data and Safety Monitoring Board]; Advisory / Consultancy: Bristol-Myers Squibb, Lilly, Genentech, Celgene, Pfizer, Merck, EMD-Serono, Boehringer Ingelheim, AstraZeneca, Novartis, Genmab, Regeneron, BioNTech, Cantargia AB, Amgen, AbbVie, Axiom, PharmaMar, Takeda, Huya Bio, GLG; Research grant / Funding (self): Millennium, Merck/Celgene, Bristol-Myers Squibb/Lilly. M.D. Hellmann: Advisory / Consultancy: Genentech, Bristol-Myers Squibb, Merck, AstraZeneca, Novartis, Janssen, Mirati, Syndax, Shattuck Labs, Immunai, Nektar, Blueprint Medicines; Research grant / Funding (institution): Bristol-Myers Squibb; Travel / Accommodation / Expenses: Bristol-Myers Squibb, AstraZeneca; Shareholder / Stockholder / Stock options: Shattuck Labs, Immunai. J. Brahmer: Advisory / Consultancy: Bristol-Myers Squibb, AstraZeneca, Genentech, Merck, Amgen. M. Reck: Honoraria (self): AbbVie, Amgen, AstraZeneca, Boehringer Ingelheim, Bristol-Myers Squibb, Celgene, Lilly, Merck, MSD, Novartis, Pfizer, Roche; Advisory / Consultancy: AbbVie, Amgen, AstraZeneca, Boehringer Ingelheim, Bristol-Myers Squibb, Celgene, Lilly, Merck, MSD, Novartis, Pfizer, Roche. S. Ramalingam: Honoraria (self): AstraZeneca, Bristol-Myers Squibb, Roche/Genentech, Loxo, Tesaro, Merck, Daichi; Advisory / Consultancy: Amgen, AbbVie, Lilly, Genentech, Takeda; Research grant / Funding (institution): Bristol-Myers Squibb, Amgen, AstraZeneca, Takeda, Advaxis, Tesaro, Merck. L. Zhang: Advisory / Consultancy: AstraZeneca, Bristol-Myers Squibb, MSD; Speaker Bureau / Expert testimony: AstraZeneca, Bristol-Myers Squibb, MSD, Roche; Research grant / Funding (institution): AstraZeneca, Bristol-Myers Squibb, Pfizer, Henrui Pharm. P. Bhagavatheeswaran: Shareholder / Stockholder / Stock options, Full / Part-time employment: Bristol-Myers Squibb. F.E. Nathan: Shareholder / Stockholder / Stock options, Full / Part-time employment: Bristol-Myers Squibb. K.J. O'Byrne: Advisory / Consultancy: Bristol-Myers Squibb, Pfizer, AstraZeneca, MSD, Roche-Genentech, Boehringer Ingelheim, Novartis, Teva, Janssen-Cilag, Natera; Speaker Bureau / Expert testimony: Bristol-Myers Squibb, Pfizer, AstraZeneca, MSD, Roche-Genentech, Boehringer Ingelheim, Janssen-Cilag, Mundipharma; Travel / Accommodation / Expenses: Bristol-Myers Squibb, Pfizer, AstraZeneca, MSD, Roche-Genentech, Boehringer Ingelheim; Shareholder / Stockholder / Stock options: Carp Pharmaceuticals, Carpe Vitae Phaemaceuticals; Licensing / Royalties: Various patents issues with licensee as listed. Queensland University of Technology and Trinity College Dublin. All other authors have declared no conflicts of interest.